CRISIS MANAGEMENT CONDUCTED BY BALI TOURISM BOARD (BTB) DURING THE MOUNT AGUNG VOLCANO ERUPTION - I Wayan Sukma Winarya Prabawa; Komang Ayu Ratika Dewi (Institut Pariwisata dan Bisnis Internasional, 2018)
This study aims to determine the implementation of crisis management, which was carried out by the Bali Tourism Board (BTB) in Bali tourism recovery efforts due to the disaster of the Mount Agung eruption. Crisis management is needed to help restore the trust of tourists and tourism industry players and minimize the impact of the crisis on the destination. This research is qualitative research by collecting data using interview methods and documentation. This research shows that the crisis that emerged in Bali's tourism sector was at a serious level, where the crisis caused losses to the Bali tourism industry, both in the form of economic losses and the image of Bali. A series of crisis management actions were carried out by BTB which was divided into 5 steps; 1) crisis identification; 2) crisis analysis; 3) crisis isolation; 4) choice of strategy; 5) controlling program.